On a Novel Modulation Cutting Process for Potassium Dihydrogen Phosphate with an Increased Brittle–Ductile Transition Cutting Depth - Yang Yang; Yu Chen; Chenyang Zhao (Machines, 2023)
Potassium dihydrogen phosphate (KDP) has garnered considerable attention due to its diverse applications across various scientific and engineering domains. Although promising machining performance enhancements have been achieved in ultra-precision diamond cutting, the brittle–ductile transition (BDT) depth for KDP crystals is essentially at the nanometer range and limits the further improvement of machining efficiency. In this paper, a novel ultra-precision diamond cutting process based on tool trapezoidal modulation is proposed for the first time to investigate the BDT characteristics of KDP crystals. By intentionally designing the tool modulation locus, the uncut chip thickness and cutting direction in the cutting duty cycle are kept constant, which provides a new strategy for probing the BDT mechanism and enhancing the machining performance. The BDT depth is significantly increased compared to the conventional ultra-precision diamond cutting owing to its unique modulation machining advantages. The significance of this paper lies not only in the improvement of the machining efficiency of KDP crystals through the proposed modulation cutting process, but also in the possibility of extending the relevant research methods and conclusions to the machining performance enhancement of other brittle optical crystals.